Design of Satellite Maneuvers for Inertia Parameter Estimation. Issue 2 (2020) - Nainer, Carlo; Gilson, Marion; Garnier, Hugues; Pittet, Christelle; Evain, Hélène
Abstract: This paper addresses the design of satellite maneuvers for the inertia estimation. The experiment design is an important step in system identification, since the choice of the excitation signal has a great influence on the precision of the parameter estimates. In order to design an optimal maneuver, the proposed method uses a cubic B-spline representation of the trajectory. The optimized maneuver is obtained through minimization of a functional based on the Fisher information matrix. The optimization process considers the physical constraints due to the saturation of the actuators. The effectiveness of the generated trajectory is evaluated via Monte Carlo simulations using the model of a satellite-type platform. Moreover, the optimized maneuver has been also tested on a real platform in a zero-gravity experiment where, due to the limited duration of the tests, the achievement of the maximum excitation is of great importance.